2015
DOI: 10.4103/1658-354x.154697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pregabalin versus ketamine in postoperative pain management in breast cancer surgery

Abstract: Background:Breast surgery compromises one of the most common cancer surgeries in females and commonly followed by acute postoperative pain. Pregabalin and ketamine have been used in many previous studies and was found to have a good analgesic profile. We assumed that pregabalin and ketamine can be used in control of postoperative pain in female patients undergoing breast cancer surgery.Material and Methods:Ninety female patients scheduled for cancer breast surgery were allocated in three groups (30 patients ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…Our results in the pregabalin group are in agreement with those of Mahran and Hassan [29] and Gupta et al, [33] who found no significant difference in the incidence of dizziness or visual disturbance in their study group compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results in the pregabalin group are in agreement with those of Mahran and Hassan [29] and Gupta et al, [33] who found no significant difference in the incidence of dizziness or visual disturbance in their study group compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Also, our results in the pregabalin group are supported by Jokela et al, [34] , Zhang et al, [27] , Kim et al, [28] , Bornemann-Cimenti et al, [31] , and Mahran and Hassan [29] , all of them reported no significant difference between pregabalin and control groups in their study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the clinic, both ketamine and butorphanol have been proven to be the effective drugs for analgesia. 7 – 9 Mahran and Hassan 21 reported that ketamine is effective in postoperative pain management in breast cancer surgery. Minoshima et al 22 also proved that ketamine could play an important role post-operation following adolescent idiopathic scoliosis surgery.…”
Section: Discussionmentioning
confidence: 99%